Religion as a form of social consciousness in philosophy (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Philosophy and faith certainly have any tasks and are essentially any forms of spiritual work. Faith is life in communion with God, with the goal of satisfying the personal need of the human soul in salvation, in finding the ultimate strength and satisfaction, unshakable peace of mind and celebration.Philosophy is essentially, unconditionally independent of any interests, a high ending comprehension of being and life by the way of discerning their absolute fundamental principle. But these, in essence, heterogeneous forms of spiritual life coincide with each other in what respect, namely, in fact, that both of them are feasible only through the assignment of consciousness to one and, in fact, what object - to God, more correctly, through living, experienced God’s discretion.
Keywords: religion, philosophy, faith, God, mind, science